Poverty Determinants in Central Lombok District and the Countermeasures Effort: in Islamic Perspective - Rizkia Laila Ramdhani (Tazkia Islamic Finance and Business Review, 2019)
This study discusses poverty determinants in Central Lombok Regency and its alleviation from Islamic Perspective. Methodologically, this study uses multiple linear regression with the Ordinary Least Squares (OLS) model and qualitative descriptive analysis. It uses secondary data obtained from the Central Statistics Agency (BPS), the National Development Planning Agency (BAPPENAS), and Regional Development Planning Agency (BAPPEDA). The result of this study shows that the population income affects the number of poor people. Therefore, the increased income of poor people to decrease poverty becomes policy recommendation in Islamic Perspective for related government in Central Lombok Regency.